2013
DOI: 10.1002/ijc.28630
|View full text |Cite|
|
Sign up to set email alerts
|

Consumption of omega‐3 fatty acids and the risk of skin cancers: A systematic review and meta‐analysis

Abstract: Skin cancers have a higher incidence than all other cancers combined and are a major cause of morbidity worldwide. Laboratory data suggest certain dietary constituents, notably omega-3 polyunsaturated fatty acids (n-3 PUFAs), could potentially protect against skin malignancy, although no large-scale review has been conducted in humans. The objective of this review and meta-analysis was to determine the relationship between dietary n-3 PUFAs and skin cancer incidence. It considered all published randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 44 publications
0
30
1
1
Order By: Relevance
“…These n‐3 and n‐6 fatty acids reduce tumor growth by inhibiting cell growth, apoptosis, angiogenesis and inflammation . Observational studies have discovered that higher levels of dietary n‐3 fatty acid intake are inversely associated with melanoma risk . A hospital‐based case–control study conducted in Italy showed that weekly consumption of fatty fish that was rich in n‐3 fatty acids was associated with a reduced risk of melanoma (odds ratio [OR] = 0.52, 95% confidence interval [CI] = 0.34–0.78).…”
mentioning
confidence: 99%
“…These n‐3 and n‐6 fatty acids reduce tumor growth by inhibiting cell growth, apoptosis, angiogenesis and inflammation . Observational studies have discovered that higher levels of dietary n‐3 fatty acid intake are inversely associated with melanoma risk . A hospital‐based case–control study conducted in Italy showed that weekly consumption of fatty fish that was rich in n‐3 fatty acids was associated with a reduced risk of melanoma (odds ratio [OR] = 0.52, 95% confidence interval [CI] = 0.34–0.78).…”
mentioning
confidence: 99%
“…Epidemiological studies regarding the association between intake or plasma concentrations of n-3 PUFAs and cancer risk reduction, provide limited and sometime contrasting data (Dahm et al, 2012;Zheng et al, 2013;Crowe et al, 2014;Noel et al, 2014). Nevertheless, in a meta-analysis and systematic review of prospective cohort studies, dietary intake of fish derived n-3 PUFAs, such as DHA and EPA, but not shorter alpha linolenic acid (ALA), was associated with a lower risk of breast cancer (Zheng et al, 2013).…”
mentioning
confidence: 99%
“…Recently, a review and meta-analysis was conducted to determine the relationship between skin cancer and dietary omega-3 intake [18]. While the data were limited, the investigators reported that intake of high omega-3 was inversely associated with melanoma (only one estimate) and SCC, although the latter was not significant.…”
Section: Baumann and Ruschmentioning
confidence: 99%